Pulmonary Manifestations of Systemic Lupus Erythematosus - Mittoo, Shikha; Fell, Charlene D. (Seminars in Respiratory and Critical Care Medicine, 2014)
Systemic lupus erythematosus (SLE) is a systemic inflammatory disease, characterized serologically by an autoantibody response to nucleic antigens, and clinically by injury and/or malfunction in any organ system. During their disease course, up to 50% of SLE patients will develop lung disease. Pulmonary manifestations of SLE include pleuritis (with or without effusion), inflammatory and fibrotic forms of interstitial lung disease, alveolar hemorrhage, shrinking lung syndrome, pulmonary hypertension, airways disease, and thromboembolic disease. Two major themes inform our understanding of SLE-associated pulmonary manifestations: first, the presence of specific autoantibodies correlates with the presence of certain pulmonary manifestations and second, vascular injury marks a common pathophysiologic thread among the various SLE-related lung diseases. This review will focus on the clinical presentation, pathogenesis, pathology, management, and prognosis of these SLE-associated lung conditions.
Keywords: systemic lupus erythematosus; lung; pleura; vascular; airways